UPAYA PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA PERPUSTAKAAN HURUF ABJAD PADA KELOMPOK A RA AS SYAFI’IYAH PONOROGO - Anugrah Dewi Nurmawati; Ida Yeni Rahmawati; Betty Yulia Wulansari (Universitas Muhammadiyah Ponorogo, 2020)
This research aims to: (1) describe and explain the process of improving children's early reading skills through the letters of the alphabet library media, (2) describing and explaining the results of improving initial reading skills achieved by children through letter library media.This type of research is a collaborative classroom action research. Subjects were 27 group A children consisting of girls and boys. The object of research is early reading skills. This research consisted of two cycles and each cycle consisted of three meetings. Data collection techniques in this research are observation and documentation. The data analysis technique was carried out in a qualitative and quantitative description.The result of this research show that early reading skill of children there are steps by step in the learning process through the alphabetical media library are: 1) Classes are formed with the format